Modulation of p53 and p21 Genes Expression in Cardiovascular Cultured Cells: Modulasi Ekspresi Gen p53 dan p21 dalam Sel Kultur Kardiovaskular - Shurooq Hussein Jaber Al Jebur (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the role of the p53 and p21 genes, central to the cell cycle arrest pathway, in cardiovascular diseases, focusing on their modulation by endocannabinoid ligands. Previous research has established the significance of CNR1 in cardiovascular regulation; however, its interaction with p53 pathways remains underexplored. We aimed to investigate the effects of Anandamide and Rimbonant on the expression levels of p53 and p21 in smooth muscle cells at both mRNA and protein levels. Our results indicate that Anandamide significantly increases p53 mRNA (3.191±0.38, Pv≤0.01) and protein (31.37±2.60) levels, while Rimbonant shows a decrease after 1 hour of treatment. Similarly, p21 expression was upregulated by Anandamide and downregulated by Rimbonant. These findings suggest that manipulating p53 activity through CNR1 ligands could potentially mitigate cardiovascular disease risks, warranting further investigation into their pharmacological applications. Highlights: Gene Modulation: Anandamide boosts p53 and p21 expression. Rimbonant Effects: Rimbonant reduces these gene levels. Therapeutic Potential: Indicates possibilities for cardiovascular disease treatment. Keywords: P53 Gene, Cardiovascular Disease, Endocannabinoids, Anandamide, Rimbonant